Disposisi Dan Keniscayaan Sebagai Modalitas Hukum Alam - Martin Suryajaya (STF Driyarkara - Diskursus, 2013)
Abstract: A debate is growing today about the ontological status of disposition in relation to the modality of natural law. This debate arose after the failure of Humean actualism to explain the basis of causality. Categoricalism tries to overcome the weaknesses of actualism by restoring the concept of disposition that is reduced to a set of categorical properties. Through such a move, categoricalism hopes to explain the basis of the disposition and yet fails to guarantee the necessity of natural law. Another alternative is to formulate a variant of dispositionalism in which dispositions are regarded as fundamental properties that are irreducible to categorical properties. Dispositionalists attempt to set up a concept of disposition which acknowledges the existence of unactualized disposition and guarantees the necessity of natural law. This essay, however, will demonstrate that dispositionalists’ solution is not free from the similar dilemma which haunts categoricalism. Keywords: Actuality, categorical property, dispositional property, supervenience, causality, finkish disposition, antidote, necessity. Abstrak: Dewasa ini berkembang perdebatan tentang status ontologis disposisi dalam kaitannya dengan modalitas hukum alam. Perdebatan ini mengemuka selepas kegagalan aktualisme Humean dalam menjelaskan landasan kausalitas. Kategorialisme mencoba mengatasi kelemahan aktualisme dengan mengembalikan konsep disposisi yang direduksi pada sekumpulan sifat kategoris. Melalui langkah ini, kategorialisme berharap dapat menerangkan landasan dari disposisi, tetapi sesungguhnya gagal mengajukan suatu konsepsi tentang hukum alam yang niscaya. Alternatifnya adalah merumuskan suatu varian dari disposisionalisme di mana disposisi adalah sifat fundamental benda yang tidak tereduksikan pada sifat kategoris. Kaum disposisionalis berupaya membangun konsepsi tentang disposisi yang, di satu sisi, mengakui adanya disposisi yang tidak teraktualisasi dan, di sisi lain, menjamin keniscayaan hukum alam. Akan tetapi, melalui artikel ini akan ditunjukkan juga bahwa solusi disposisionalis tersebut tidak lepas dari dilema serupa yang menghantui kategorialisme. Kata-kata Kunci: Aktualitas, sifat kategoris, sifat disposisional, kebertopangan, kausalitas, disposisi-pelenyapan, penawar, keniscayaan.